2014
DOI: 10.1016/j.ejim.2014.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Gender-differences in disease distribution and outcome in hospitalized elderly: Data from the REPOSI study

Abstract: Our study showed a gender dimorphism in the demographic and morbidity profiles of hospitalized elderly people, emphasizing once more the need for a personalized process of healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 45 publications
7
50
2
7
Order By: Relevance
“…Corrao et al (17) found a prevalence of chronic disease in 55%-98% of people aged >65 years, and 97.9% of the elderly had chronic diseases. The current study revealed that chronic diseases were observed more often in low-and middle-income countries (2), and the elderly living in rural areas were more prone to developing chronic diseases (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corrao et al (17) found a prevalence of chronic disease in 55%-98% of people aged >65 years, and 97.9% of the elderly had chronic diseases. The current study revealed that chronic diseases were observed more often in low-and middle-income countries (2), and the elderly living in rural areas were more prone to developing chronic diseases (18).…”
Section: Discussionmentioning
confidence: 99%
“…Corrao et al (17) reported that women live longer and outnumber men. In contrast, older women develop more chronic diseases, and being female, older, and having a low socioeconomic level are associated with multimorbidity and an increased risk for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the REPOSI registry indicate a prevalence of heart failure close to 30% in COPD patients aged >65 years with comorbidities [3].…”
Section: Copd and Cardiovascular Comorbiditiesmentioning
confidence: 99%
“…It results in a substantial waste of economic resources, in particular from dealing with exacerbations and hospitalisations [2,3]. COPD is becoming more widespread in both industrialised and developing countries, with its prevalence reaching ∼5% in Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation